ABO, Rh, Gene Frequency: A Comparative Study between Different Countries (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
People have always been fascinated by blood, ancient Egyptians bathed in it, Aristocrats drank it. Currently, 30 different blood group systems are known, 9 of which are considered to be the major blood group systems. The ABO and Rh blood groups are among the most important blood groups. Different population exhibits significant differences in the frequency of each blood group, so the aim of this work is to study the geographic variation and prevalence of ABO blood group, Rh factor and gene frequency of ABO blood group and Rh factor. The study was done on medical students from Egypt (Faculty of Medicine in Menofiya University), Libya (Faculty of Medicine in El Zawya-Al Gabal Algharby University) and India (Government Medical Collage Kashmir). ABO blood group and Rh were done by standard rapid tile method. The result of this study showed that blood group ‘O’ was the most prevalent in Libya and India (48.9% and 40.8%, respectively) followed by group A (37.9%) and group B (12.8%) in Libya, in India, A (20.9%) is second in prevalence followed by B (31.6%). In Egypt, blood group A (37.9%) is the most prevalent one, which is in contrast to previous studies were O was the most prevalent, which is now in second place (27%), followed by B (25.1%). All the three countries showed AB as the least common blood group in its population with the predominance of Rh positive. Expected A gene frequency in Egypt is the highest one (0.279), followed by Libya (0.214) and India (0.149). Gene B frequency is more prevalent in India then Egypt and Libya (0.215, 0.195 and 0.094, respectively), while O gene is more frequent in Libya (0.962), then India (0.637) and Egypt (0.526). In Libya and India, males showed high frequent blood group O (44.9% and 44.5%, respectively), while in Egypt both males and females showed high frequency of blood group A (41.7% and 33.3%, respectively). This work concluded that blood group O is the commonest blood group in Libya and India, whereas in Egypt there is a shift from previous prevalence of O blood group to now A. More than 85% of the population is Rhesus positive in all the three countries. A gene is more frequent in Egypt, B gene is more in India, while O gene is more in Libya. There is significant relation between ABO and gender.
Keywords: ABO blood groups; Rhesus; Variation; Population; Regions